ANALISIS KEMAMPUAN STORY TELLING GURU DALAM PENYAMPAIAN MATERI SEJARAH DI MAN 2 PONTIANAK - Sarmina Sarmina; Aminuyati Aminuyati; Ika Rahmatika Chalim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research to determine the analysis of the teacher's story telling ability indelivering historical material at MAN 2 Pontianak. The method used isqualitative in the form of case study research. The results showing that 1. Theteacher's story telling ability in delivering history material can’t do optimallybecause some indicators in story telling can’t displayed or raised. This wasbecause the teacher can’t interact directly with students when delivering storytelling online. The obstacle faced by a teacher when doing story telling is theteacher can’t choose the place where the story is supposed to be, the teachercan’t bring up all the characters in the story, and students not serious aboutstudying 3. Solutions to overcome the problem of choosing a place to tellstoriesand bring up the characters in the story when doing story telling canbe resolved when covid-19 is no longer there. Thus the teacher will find iteasier tochoose a place to tell stories and interact directly with students. Theteacher rebukes students when not seriously studying and instructs students torepeat the stories that have been told.Keywords: Teacher Ability, Story Telling, History Learning